The Evaluation of the Behaviors of Students Through Problem-solving Process for 3rd-year Secondary Students at Satid Secondary School - PHATTHANA, Bounyong; VATHANAVONG, Thongthiane; VONGSIPASEUTH, Bounmor; KHAMPADITH, Shaidan; MOUNGKHOUNSAVAT, Phoutthasay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The research focuses on enhancing students' problem-solving abilities on mathematics through problem solving processes. The target group consists of 39 third-year secondary students, including 19 females, at Demonstration Secondary School, Luang Prabang Teacher Training College. The research employed observation checklists to monitor and assess the students' activities and progress in their problem-solving processes. The checklist used for data collection is divided into three main areas: 1) problem-solving skills, 2) collaboration and communication, and 3) leadership and attitude. The findings indicated that student behaviors in each area of the problem-solving process overall showed a slight improvement, measured across five sessions. The average scores for problem-solving skills, collaboration and communication, and leadership and attitude were 1.00, 1.08, and 1.27, respectively. Nevertheless, it can be concluded that adopting a teaching method focused on problem-solving processes can gradually enhance students' problem-solving skills.